Analysis of the Effectiveness of E-Marketing Strategies in Increasing Brand Awareness in FMCG Industry MSMEs - Feri Andika Prasetya; Kevin Ghulaman Silmi; Kuncoro Aprilia Hikmawati; Lili Purwanitasari; Titis Shinta Dhewi (Maneggio, 2025)
This study aims to analyze the effectiveness of e-marketing strategies in increasing brand awareness among Micro, Small, and Medium Enterprises (MSMEs) in the Fast-Moving Consumer Goods (FMCG) sector. In the digital era, MSMEs are increasingly required to adapt to technological developments, particularly in marketing. However, many business actors still lack the understanding to implement digital strategies effectively. This study focuses on four key e-marketing components: social media marketing, SEO/SEM, content marketing, and email marketing. Using a quantitative approach, data were collected from 109 MSME respondents using purposive sampling, and analyzed through Structural Equation Modeling (SEM) with SmartPLS. The results show that social media marketing and SEO/SEM have a significant and positive effect on brand awareness, while content marketing and email marketing show no significant effect. These findings suggest that MSMEs should prioritize the use of social media and search engine optimization strategies to enhance brand visibility. This study provides valuable insights for MSME practitioners in formulating effective digital marketing strategies and contributes to the academic literature on MSME marketing performance in the digital economy era.